Hubungan Kekuatan Karakter dan kebahagiaan pada Suku Betawi - Firda Khalisa; Imelda Ika Dian Oriza; Fivi Nurwianti (Jurnal Ilmiah Psikologi MIND SET, 2010)
The study aimed to examine the relationship between well-being and character strength in Betawi ethnic group. It used non-experimental design, particularly field study with incidental sampling technique. Respondents were 184 adults of Betawi ethnic group, 18-55 of years, had minimum high school background and resided in greater Jakarta. The researchers developed a tool to measure strength of characters which was adapted from VIA-IS created by Peterson and Seligman. The result of the study based on multiple regression calculation revealed that character strength and well being had positive correlation of 0.674 (significance .000). Character strength contributed 45.4% to well being of Betawi people. Significant contributors were, among others, persistence, hope, and integrity, while the five crucial character strength found in Betawi ethnic group were gratitude, kindness, citizenship, fairness and integrity.